ST08 Altered NF-κB Pathway in Breast Cancer Cells In Vitro as Revealed by miRNA-mRNA Analysis and Enhanced the Effect of Cisplatin on Tumour Reduction in EAC Mouse Model - Nirgude, Snehal; Desai, Sagar; Mahadeva, Raghunandan; Ravindran, Febina; Choudhary, Bibha (Frontiers in Oncology, 2022)
ST08 is a novel curcumin derivative that exhibited apoptotic and anti-migratory activity in MDA-MB-231, triple-negative breast cancer cells reported earlier. ST08 reduced tumor burden in vivo and induced apoptosis through the mitochondrial pathway both ex vivo and in vivo. ST08 potentiated the effect of cisplatin in vitro and in vivo in mouse EAC breast cancer models without any apparent toxicity. ST08 induced alterations in the gene expression were studied by parallel analysis of miRNA and mRNA. 74 differentially expressed miRNA regulated 114 mRNA in triple-negative(MDA-MB-231) cancer cells. Pathway related to the ECM was altered in mesenchymal MDA-MB-231 cells. We constructed a unique miRNA-mRNA interaction network, and one of the pathways regulated by miRNA was NF-KB. Targets of NF-KB like MMP1, PTX3, and MMP2 were downregulated in MDA-MB-231 in response to ST08 treatment. PMA induced cell proliferation was abrogated by ST08 treatment validating regulation of NF-KB in breast cancer.